2008
DOI: 10.1177/1078087407308516
|View full text |Cite
|
Sign up to set email alerts
|

Tax Increment Financing and Property Value

Abstract: This paper examines the impact of tax increment financing (TIF) on business property value. Using parcel-level data from Milwaukee, Wisconsin, from 1980 to1999, a semilog econometric model is estimated using fixed effects regression. A two-stage estimation process is also used to test and correct for potential self-selection bias and endogeneity associated with TIF implementation. The findings suggest that the provision of public services offered within TIF districts is capitalized into business property value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 19 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…This led him to suggest that TIF may be a budget manipulation not an economic development tool. In a study of Milwaukee TIF districts, Carroll (2008) found that the growth of business property value within the TIF district is attributable to the capitalization of higher quality public services offered in these districts. Dardia (1988) reviewed and analyzed the use of TIF in California's Redevelopment Area (RDA)'s.…”
Section: Tif and Economic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…This led him to suggest that TIF may be a budget manipulation not an economic development tool. In a study of Milwaukee TIF districts, Carroll (2008) found that the growth of business property value within the TIF district is attributable to the capitalization of higher quality public services offered in these districts. Dardia (1988) reviewed and analyzed the use of TIF in California's Redevelopment Area (RDA)'s.…”
Section: Tif and Economic Activitymentioning
confidence: 99%
“…In a study of Wisconsin TIF districts, Skidmore, Merriman, and Kashian (2009) determined that about half the annexations in Wisconsin at the time were of recent TIF districts. In a study of Milwaukee TIF districts, Carroll (2008) found that the growth of business property value within the TIF district is attributable to the capitalization of higher quality public services offered in these districts. Smith (2009) reports a similar effect in Chicago, with neighborhood quality influencing the magnitude of the impacts on commercial property values.…”
Section: Tif and Economic Activitymentioning
confidence: 99%
“…1 TIF also has the potential to drain needed revenue from other taxing jurisdictions, especially school districts (Weber, Bhatta, and Merriman 2003). However, others argue that TIF can indeed help property value growth, in terms of aggregate residential and commercial property values (Carroll 2008;Man 2001;Merriman, Skidmore, and Kashian 2008;Smith 2006), and has been used successfully to offset deleterious property value effects from crime and brownfields (Carroll and Eger 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Impacts of public investments, public services, or public land use on surrounding private land has been assessed both scientifically and empirically throughout last years (Ayougu, 2007;Bhatta and Drennan, 2003;Weber et al, 2003;Canning and Pedroni, 2008;Carroll, 2008;Haughwout, 2002;Mikelbank, 2004;Moreno and Lopez-Bazo, 2007;Siethoff and Kockelman, 2002;Smith and Gihring, 2006;Taylor and Brown, 2006;Walters, 2011Walters, , 2012aWalters, , 2012b.…”
Section: Theoretical Frameworkmentioning
confidence: 99%